Older nurses' experiences of providing direct care in hospital nursing units: a qualitative systematic review. (March 2018) - Parsons, Karen; Gaudine, Alice; Swab, Michelle
ABSTRACT: Background: Most developed countries throughout the world are experiencing an aging nursing workforce as their population ages. Older nurses often experience different challenges then their younger nurse counterparts. With the increase in older nurses relative to younger nurses potentially available to work in hospitals, it is important to understand the experience of older nurses on high paced hospital nursing units. This understanding will lend knowledge to ways of lessening the loss of these highly skilled experienced workers and improve patient outcomes. Objectives: To identify, evaluate and synthesize the existing qualitative evidence on older nurses' experiences of providing direct care to patients in hospital nursing units. Inclusion criteria: The review considered studies which included registered nurses 45 years and over who work as direct caregivers in any type of in-patient hospital nursing unit. The phenomenon of interest was the experience of older nurses in providing direct nursing care in any type of in-patient hospital nursing unit (i.e. including but not limited to medical/surgical units, intensive care units, critical care units, perioperative units, palliative care units, obstetrical units, emergency departments and rehabilitative care units). The review excluded studies focussing entirely on enrolled nurses, licensed practical nurses and licensed vocational nurses. Types of studies : Qualitative data including, but not limited to the following methodologies: phenomenology, grounded theory, ethnography, action research and feminist research. Methods: The databases CINAHL, PubMed, PsycINFO, Embase, AgeLine, Sociological Abstracts and SocINDEX were searched from inception; the search was conducted on October 13, 2017; no date limiters or language limiters were applied. Each paper was assessed by two independent reviewers for methodological quality using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Qualitative Research. Any disagreements that arose between the reviewers were resolved through discussion. Data extraction was conducted by two independent reviewers using the standardized qualitative data extraction tool from JBI. The qualitative research findings were pooled using JBI methodology. The JBI process of meta-aggregation was used to identify categories and synthesized findings. Results: Twelve papers were included in the review. Three synthesized findings were extracted from 12 categories and 75 findings. The three synthesized findings extracted from the papers were: (1) Love of nursing: It's who I am and I love it; (2) It's a rewarding but challenging and changing job; it's a different job and it can be challenging; (3) It's a challenging job; can I keep up? Conclusions: Older nurses love nursing and have created an identity around their profession. They view their profession positively and believe their job to be unlike any other, yet they identify many ongoing challenges and changes. Despite their desire to continue in their role they are often faced with hardships that threaten their ability to stay at the bedside. A key role of hospital administrators to keep older nurses in the workplace is to develop programs to prevent work related illness and to promote health. Given the low ConQual scores in the current systematic review, additional research is recommended to understand the older nurses' experience in providing direct care in hospital nursing units as well as predicting health age of retirement and length of bedside nursing.